2004
DOI: 10.1016/j.jacc.2004.02.052
|View full text |Cite
|
Sign up to set email alerts
|

The calcium sensitizer levosimendan improves the function of stunned myocardium after percutaneous transluminal coronary angioplasty in acute myocardial ischemia

Abstract: Levosimendan improved the function of stunned myocardium without obvious impairment of diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(122 citation statements)
references
References 30 publications
7
103
0
12
Order By: Relevance
“…Also, levosimendan was effective in detecting contractile reserve even in the proportion of patients with ischaemic LV dysfunction who had no clear evidence of contractile reserve with dobutamine. Our results are in keeping with a recent study which showed that a 10-minute infusion of 24 μg/kg of levosimendan induced a significant improvement of contractility in stunned myocardium measured 20 min after the end of the infusion [9]. A clinical implication from our trial is that revascularisation may be beneficial in some patients not responding to dobutamine, but our findings need confirmation in a larger study.…”
Section: Resultssupporting
confidence: 91%
“…Also, levosimendan was effective in detecting contractile reserve even in the proportion of patients with ischaemic LV dysfunction who had no clear evidence of contractile reserve with dobutamine. Our results are in keeping with a recent study which showed that a 10-minute infusion of 24 μg/kg of levosimendan induced a significant improvement of contractility in stunned myocardium measured 20 min after the end of the infusion [9]. A clinical implication from our trial is that revascularisation may be beneficial in some patients not responding to dobutamine, but our findings need confirmation in a larger study.…”
Section: Resultssupporting
confidence: 91%
“…Besides these, levosimendan enhances coronary vasodilatation via the nitric oxide-dependent pathway, which inhibits phosphodiesterase-3 and contributes to the protection of the myocardium from ischemia by means of increasing the coronary blood flow (12,13). It has been demonstrated that levosimendan improves the myocardial systolic function in patients with a stunned myocardium who underwent percutaneous coronary intervention due to acute myocardial infarction (14).…”
Section: Discussionmentioning
confidence: 99%
“…22 Moreover, a recent study demonstrated that levosimendan is safe in patients with acute coronary syndromes who underwent a percutaneous coronary intervention (PCI) and improves the function of stunned myocardium. 23 Safety, efficacy, and effects on mortality of levosimendan in patients with LV failure complicating AMI were investigated in the RUSSLAN study. 24 There were no significant differences among the treatment groups in the proportion of patients who experienced clinically important ischemia in this study.…”
Section: Discussionmentioning
confidence: 99%